Production of fish feed from palm oil waste using fermentation technology in Terak Village - Nurzaidah Putri Dalimunthe; Sujadi Priyansah; Feni Kurnia; Randi Syafutra (Community Empowerment, 2023)
An approach to get around difficulties in discovering reasonable feed materials is to use ex-mining land and palm oil waste in fish farming. This affects the minimal outcomes and profits realized from the business operations. In order to improve the quality of fish farming products, this community service aims to improve the community's knowledge and expertise regarding the use of waste palm oil as fish food. Training sessions using the lecture method, practice sessions, and mentoring are used to provide this program. After this program, the partners' understanding of processing palm oil waste as a source of fish farming feed improved, which enabled them to increase profits from their business.